Analysis earning management, good corporate governance, on sticky cost behavior through the policy tax incentives - Jefrianus Jehadu; Aloisius Hama (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to test empirically the effect of Earning management, Good Corporate Governance, on sticky cost behavior through a tax incentive policy. The type of data used for sampling is purposive sampling and hypothesis testing using the Partial Least Square (PLS) analysis model with the help of SmartPLS version 3.0 for windows software. The results of this study are; Earning management has contributed to Sticky Cost Behavior. Good Corporate Governance has contributed to Sticky Cost Behavior. Tax incentive policies are not proven as a moderating variable in the influence of Earning management target Sticky Cost. _ The tax incentive policy is proven to be a moderating variable in influence Good Corporate Governance Against Sticky Cost Behavior.